RETRACTED: Black Soldier Fly (Hermetia illucens), a source of antimicrobial peptides - Shevchenko Natalia; Guseva Yulia; Vasiliev Alexey; Pigina Svetlana; Dlusskaya Yulia; Bagdasarian Elina (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001